Tutorial action plan and its contribution to a university study program (Revista Electrónica Calidad en la Educación Superior, 2021)
A tutorial action plan is a coordinated activity that involves members of the educational community. The effects of a tutorial action plan on students' academic progress, in its personal, academic and professional dimensions, were studied. We worked with 59 obstetrics students in the year 2018 from the Universidad Nacional De San Cristóbal de Huamanga-UNSCH, Peru. The design was quasi-experimental, with pre-test - intervention - post-test. Workshops were organized: induction, curriculum, study methods, information reinforcement, feedback and evaluation of achievement of competencies with the help of teachers. It was demonstrated that students, before the intervention, showed attitudes with limitations in soft skills in the work activities, after the intervention significant improvements were observed in all attitudes.
Keywords: Tutorial action plan; Competencies; Leadership; Soft skills